Consumer Lifestyle Approach to Quantify CO2 Emissions Caused by Domestic Washing Clothes (Journal of Fiber Bioengineering and Informatics, 2013)
Household CO_2 emissions are gaining more attention from researchers in recent years. Domestic washingis an important household routine and one of the main sources of household CO_2 emissions. In this paper,Consumer Lifestyle Approach (CLA) was used to quantify CO_2 emissions from domestic washing. Aninvestigation of 493 families, from 16 cities out of 8 provinces in China, was held to study the five mainhousehold characteristics including the demographic composition, living condition, family income andexpenditure, education level and most importantly, laundry habit. The relationship between domesticwashing characteristics and CO_2 emissions is concluded from multi-variable linear return analysis. Theresults show that family's washing frequency as well as washing machine's efficiency and capacity aremajor factors which affect CO_2 emissions. Other factors such as per capita living space, family workingpopulation and education level also have an influence to a certain extent.
Keywords: Domestic Washing; CO_2 Emissions; CLA; Multi-variable Linear Return Analysis